HIV-1 recruits UPF1 but excludes UPF2 to promote nucleocytoplasmic export of the genomic RNA - Ajamian, Lara; Abel, Karen; Rao, Shringar; Vyboh, Kishanda; García-de-Gracia, Francisco; Soto-Rifo, Ricardo; Kulozik, Andreas; Gehring, Niels H.; Mouland, Andrew J. (Biomolecules, 2015)
Unspliced, genomic HIV-1 RNA (vRNA) is a component of several ribonucleoprotein complexes (RNP) during the viral replication cycle. In earlier work, we demonstrated that the host upframeshift protein 1 (UPF1), a key factor in nonsense-mediated mRNA decay (NMD), colocalized and associated to the viral structural protein Gag during viral egress. In this work, we demonstrate a new function for UPF1 in the regulation of vRNA nuclear export. OPEN ACCESS Biomolecules 2015, 5 2809 We establish that the nucleocytoplasmic shuttling of UPF1 is required for this function and demonstrate that UPF1 exists in two essential viral RNPs during the late phase of HIV-1 replication: the first, in a nuclear export RNP that contains Rev, CRM1, DDX3 and the nucleoporin p62, and the second, which excludes these nuclear export markers but contains Gag in the cytoplasm. Interestingly, we observed that both UPF2 and the long isoform of UPF3a, UPF3aL, but not the shorter isoforms UPF3aS and UPF3b, are excluded from the UPF1-Rev-CRM1-DDX3 complex as they are negative regulators of vRNA nuclear export. In silico protein-protein docking analyses suggest that Rev binds UPF1 in a region that overlaps the UPF2 binding site, thus explaining the exclusion of this negative regulatory factor by HIV-1 that is necessary for vRNA trafficking. This work uncovers a novel and unique regulatory circuit involving several UPF proteins that ultimately regulate vRNA nuclear export and trafficking.
Gesehen am 14.10.2020